A rare cause of atypical facial pain - Suzannah Hall; Kevin Michell; David Howlett (Clinical Medicine)
This case illustrates a rare cause of facial pain due to glossopharyngeal neuralgia in a 66-year-old male patient. Imaging confirmed an aneurysm of the cervical internal carotid artery as the cause; the aneurysm itself, likely secondary to an elongated styloid process (Eagle's syndrome). The imaging findings and management options are discussed below.